Mapping the human phosphatome on growth pathways - Francesca Sacco; Pier Federico Gherardini; Serena Paoluzi; Julio Saez‐Rodriguez; Manuela Helmer‐Citterich; Antonella Ragnini‐Wilson; Luisa Castagnoli; Gianni Cesareni (Molecular Systems Biology)
Abstract Large‐scale siRNA screenings allow linking the function of poorly characterized genes to phenotypic readouts. According to this strategy, genes are associated with a function of interest if the alteration of their expression perturbs the phenotypic readouts. However, given the intricacy of the cell regulatory network, the mapping procedure is low resolution and the resulting models provide little mechanistic insights. We have developed a new strategy that combines multiparametric analysis of cell perturbation with logic modeling to achieve a more detailed functional mapping of human genes onto complex pathways. A literature‐derived optimized model is used to infer the cell activation state following upregulation or downregulation of the model entities. By matching this signature with the experimental profile obtained in the high‐throughput siRNA screening it is possible to infer the target of each protein, thus defining its ‘entry point’ in the network. By this novel approach, 41 phosphatases that affect key growth pathways were identified and mapped onto a human epithelial cell‐specific growth model, thus providing insights into the mechanisms underlying their function.